2019
DOI: 10.3102/0034654319843494
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Mathematics Anxiety and Mathematics Performance Among School-Aged Students: A Meta-Analysis

Abstract: The purpose of this meta-analysis was to examine the relation between mathematics anxiety (MA) and mathematics performance among school-aged students, and to identify potential moderators and underlying mechanisms of such relation, including grade level, temporal relations, difficulty of mathematical tasks, dimensions of MA measures, effects on student grades, and working memory. A meta-analysis of 131 studies with 478 effect sizes was conducted. The results indicated that a significant negative correlation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
4
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(276 citation statements)
references
References 166 publications
15
164
4
12
Order By: Relevance
“…Some studies have shown that math anxiety difficulties are specifically related to tasks with numerical information (Ashcraft and Kirk, 2001) or to dysfunctional math-related contexts (Shi and Liu, 2016). In fact, Namkung et al (2019) in a recent metaanalysis pointed out that only those WM tasks that involve numerical information may prompt math anxiety. As such, the results in the present study may not be generalised to other types of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that math anxiety difficulties are specifically related to tasks with numerical information (Ashcraft and Kirk, 2001) or to dysfunctional math-related contexts (Shi and Liu, 2016). In fact, Namkung et al (2019) in a recent metaanalysis pointed out that only those WM tasks that involve numerical information may prompt math anxiety. As such, the results in the present study may not be generalised to other types of information.…”
Section: Discussionmentioning
confidence: 99%
“…A highly convenient feature of this task for the present study is that it employs numerical information and operations with which math-anxious individuals encounter difficulties (Suárez-Pellicioni et al, 2016). Indeed, Namkung et al (2019) have suggested that the relationship between math anxiety and WM is domain-specific: only the tasks that involve numbers would induce math anxiety that in turn disrupts the functioning of WM.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics Anxiety (MA) has a substantial impact on many students' academic and personal lives. It influences achievement in mathematics tests and classes (Hembree, 1990;Ma, 1999;Namkung, Peng, & Lin, 2019). Moreover, students with high MA avoid mathematics in everyday life as well as in career and academic choices (Dowker, Sarkar, & Looi, 2016;Ma, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of more applied research on numerical cognition include evaluations of effectiveness of interventions in early childhood (Mononen et al, 2014;Wang et al, 2016;Christodoulou et al, 2017;Nelson and McMaster, 2019); for older students (Jitendra et al, 2018;Stevens et al, 2018); across age groups (Dennis et al, 2016); and across different regions of the world (Conn, 2017). Other examples include interventions for students with emotional difficulties (Losinski et al, 2019); math anxiety (Namkung et al, 2019); or on attitudes toward achievement (Savelsbergh et al, 2016); the impact of homework (Fan et al, 2017); and specific teaching strategies (Capar and Tarim, 2015;Rittle-Johnson et al, 2017;Guillaume and Van Rinsveld, 2018).…”
Section: More Basic and More Applied Research On Numerical Cognitionmentioning
confidence: 99%